1994
DOI: 10.1037/0022-006x.62.4.783
|View full text |Cite
|
Sign up to set email alerts
|

Assessing predictions of violence: Being accurate about accuracy.

Abstract: The prediction of violence occupies a prominent and controversial place in public mental health practice. Productive debate about the validity of violence predictions has been hampered by the use of methods for quantifying accuracy that do not control for base rates or biases in favor of certain outcomes. This article describes these problems and shows how receiver-operating characteristic analysis can be used to solve them. The article also reanalyzes 58 data sets from 44 published studies of violence predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
524
1
14

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 654 publications
(555 citation statements)
references
References 37 publications
10
524
1
14
Order By: Relevance
“…This previous research has shown clinical testimony to be more persuasive than actuarial testimony, despite the overall inferiority of clinical testimony in predicting violence (Borum, 1996;Gardner et al, 1996;Mossman, 1994;Quinsey et al, 1998). According to cognitive-experiential self-theory (CEST), this pattern of results may be due to the relative influence of experiential over rational information processing.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This previous research has shown clinical testimony to be more persuasive than actuarial testimony, despite the overall inferiority of clinical testimony in predicting violence (Borum, 1996;Gardner et al, 1996;Mossman, 1994;Quinsey et al, 1998). According to cognitive-experiential self-theory (CEST), this pattern of results may be due to the relative influence of experiential over rational information processing.…”
Section: Discussionmentioning
confidence: 98%
“…the type of the prediction offered by the expert psychiatrist in the Barefoot case) are unreliable (Grisso & Appelbaum, 1992;Faust & Ziskin, 1988;Hart, Webster, & Menzies, 1993;Melton et al, 1997;Monahan, 1981;Monahan & Steadman, 1994;Otto, 1992;Showalter, 1990), more recent research suggests they are not as inaccurate as was portrayed in the Barefoot case (Mossman, 1994; his meta-analysis suggests false positive rates closer to 44%), and clinical predictions may be equal to other methods of dangerousness prediction for very short time periods (McNeil, Sanders, & Binder, 1998;Mossman, 1994).…”
Section: Advances In Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…post-release sexual or non-sexual violence; Mossman, 1994). Thus, receiver operating characteristic (ROC) analyses were also performed to evaluate the ability of instrumentinformed clinical judgments to predict recidivism, as well as to evaluate the predictive validity of these judgments across confidence groups.…”
Section: Receiver Operating Characteristic Analysesmentioning
confidence: 99%
“…Even though many studies have been able to demonstrate the superior predictive accuracy of both actuarial methods (Bonta, Law, & Hanson, 1998;Grove, Zald, Lebow, Snitz, & Nelson, 2000;Hilton & Simmons, 2001;Mossman, 1994;Rice & Harris, 1997;Swets, Dawas, & Monahan, 2000) and systematic content-relevant self-report procedures (Walters, 2006) over clinical and intuitive methods, most mental health professionals in Germany, Switzerland, and Austria still use these methods (Urbaniok et al, 2006).…”
Section: Introductionmentioning
confidence: 99%